An injectable and conductive TEMPOL/polypyrrole integrated peptide co-assembly hydrogel promotes functional maturation of cardiomyocytes for myocardial infarction repair. (1st May 2022) - Zhan, Jie; Liao, Xu; Fan, Xianglin; Zhang, Jianwu; Li, Hekai; Cai, Yanbin; Qiu, Xiaozhong
Abstract: A cell-implantation strategy offers a promising paradigm for cardiac repair after myocardial infarction (MI). However, the hostile reactive oxygen species (ROS) microenvironment in infarcted zone hinders the survival and maturation of implanted cells and affects the ultimate therapeutic outcome. Besides, the generation of fibrosis scarring deprives the myocardium of electrical communications and induces cardiac dysfunction, eventually resulting in heart failure. Herein, an injectable ROS-scavenging/conductive composite hydrogel (R&C-Gel) was constructed via specific binding between conductive polypyrrole (PPy) and multi-component co-assembly peptides. Integrating antioxidant TEMPOL into the peptide endows it with strong ROS-eliminating ability, and the nanoengineering of polypyrrole (PPy) by wet milling facilitates PPy uniformly binding to the target T59 peptide in nanofibers. The thixotropy of co-assembly hydrogels confirmed by rheology and the macroporous structure of the R&C-Gel surface observed by SEM together suggest that the R&C-Gel could be an ideal vehicle for cell engraftment. The antioxidant ability and electroconductivity of the R&C-Gel were verified. In vitro experiments demonstrated that the R&C-Gel could efficiently remove ROS in cardiomyocytes and reduce apoptosis under oxygen-glucose deprivation (OGD) conditions. The rhythmic intracellular Ca 2+ puffs and expression of Cx-43 protein further proved the R&C-Gel could enhance the electrical and contractile performance of cardiomyocytes. Echocardiography and histological analysis convincingly revealed that the R&C-Gel-combined cardiomyocytes significantly promoted cardiac repair and rebuilt cardiac function, such as reducing apoptosis, accelerating gap junction formation, increasing ejection fraction, and decreasing the fibrosis area. This study provides new insight into the design and construction of multifunctional conductive hydrogels for cardiac tissue engineering. Highlights: An injectable composite hydrogel (R&C-Gel) is prepared via specific binding between conductive PPy and multi-component peptides. Integrating the TEMPOL endows the R&C-Gel with strong ROS-eliminating ability to reduce the apoptosis of CMs under hypoxia. Nanoengineering of vapor-polymerized PPy membrane to conductive NanoClusters facilitates PPy uniformly binding to nanofibers of R&C-gel. R&C-Gel promotes rhythmic intracellular Ca 2+ puffs and the expression of Cx-43 protein in the maturation of CMs. Injection of CMs@R&C-Gel is capable of restoring cardiac function post-MI.